Triplet Delivery following Unilateral Twin Salpingocyesis - Johnson O. Komolafe; Rasaq A. Akindele; Adeniyi O. Fasanu; Callistus A. Akinleye; Taiwo O. Akinbile; Monisayo O. Komolafe; Muyiwa O. Oguntunde (Case Reports in Obstetrics and Gynecology)
We present the case of a 36-year-old woman with primary infertility of six-year duration who had IVF/ICSI on account of male factor infertility. Transvaginal scanning done on the 30th day following embryo transfer revealed an empty uterine cavity with two gestational sacs containing active fetal echoes in the right adnexum. Patient reluctantly had right salpingectomy via open laparatomy. The patient had repeat embryo transfer eleven months afterwards that culminated in the delivery of living twins with a fetal papyraceous.